Elderly Husbands Caring at Home for Wives diagnosed with Alzheimer's disease: Are male caregivers really different? - Cahill, Suzanne (My University, 2000)
In Australia, there is a dearth of literature available on men as principal carers despite reports which show that in the 60 + age group, looking after a sick spouse becomes the major form of caregiving and men as carers predominate (ABS, 1993). The paper reports findings from a study of 26aged husbands who cared at home for their cognitively impaired wives, tn-depth interviews collected quantitative and qualitative data about men's caregiving experiences. Findings challenge the literature about the role gender plays in evoking care and service responses. Results show how men demonstrated a strong injunction to care, performed intimate personal care tasks competently, received limited government support and derived some satisfaction from the caregiving role. Despite similarities between male and female caregivers being noted, some gender differences in the way in which men approached the care role are described. The need for community care policies to be more sensitive to the gendered context of elderly care provision is discussed.
PUBLISHED
Keywords: Ageing; FAMILY; Families & Social Change; OLDER PEOPLE; Social Work; Training and Development; Age-related disability; Chronic Health Condition; Relationships